2006
DOI: 10.1088/0957-4484/17/10/039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing atmosphere on the magnetism of Zn1−xCoxO (0≤x≤0.10) nanoparticles

Abstract: Abstract:We report the crystal structure and magnetic properties of Zn 1-x Co x O (0 ≤ x ≤ 0.10) nanoparticles synthesized by heating metal acetates in organic solvent. The nanoparticles were crystallized in wurtzite ZnO structure after annealing in air and in a forming gas (Ar95%+H5%). The X-ray diffraction and Xray photoemission spectroscopy (XPS) data for different Co content show clear evidence for the Co +2 ions in tetrahedral symmetry, indicating the substitution of Co +2 in ZnO lattice. However samples … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
106
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(125 citation statements)
references
References 31 publications
18
106
1
Order By: Relevance
“…It has been observed that the energy band gap decreases with increase in the lattice parameter [27]. This explanation is consistent with our observation [10] [26,29] that are responsible for the increased absorption that is manifested as a step in the reflectance. In our case the presence of this step suggests that the addition of Co in ZnO leads to the formation of defect levels close to the conduction band edge.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It has been observed that the energy band gap decreases with increase in the lattice parameter [27]. This explanation is consistent with our observation [10] [26,29] that are responsible for the increased absorption that is manifested as a step in the reflectance. In our case the presence of this step suggests that the addition of Co in ZnO leads to the formation of defect levels close to the conduction band edge.…”
Section: Resultssupporting
confidence: 92%
“…The magnetic properties of both types of samples, those annealed in air and in forming gas, have been reported earlier [10]. Only those samples exhibited ferromagnetism which had been annealed in a forming gas and show clear hysteresis loops with coercivity and remanence at 300 K. However, no evidence of ferromagnetism was found in air annealed samples down to 10K, the lowest temperature investigated.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…While Alaria and his co-workers [12] reported that by adding Al ions in Co-doped ZnO using co-precipitation method could increase the concentration of free carriers, but the magnetic properties showed no evolution and no evidence of ferromagnetism. It was also reported by Naeem et al that only Co-doped ZnO samples annealed in the reducing atmosphere of the forming gas, that showed the presence of oxygen vacancies, exhibited ferromagnetism at RT [13]. Therefore, further investigations are needed to figure out these discrepancies and confirm the origin of ferromagnetism in ZnO based DMSs.…”
Section: Introductionmentioning
confidence: 91%
“…The LBEC is assigned to the intrinsic O 2-ions present in a wurtzite structure of hexagonal Zn 2+ ion arrays, while HBEC is ascribed to oxygen vacancies in the oxygen-deficient regions of the material. 9 Another notable observation made from O 1s XPS spectrum is that HBEC became pronounced after Ar sputtering in AIP Advances 2, 012182 (2012) comparison to that as-grown sample. This is possibly due to loss of oxygen by Ar + bombardment on the samples.…”
Section: Methodsmentioning
confidence: 96%